2020
DOI: 10.1093/cid/ciaa1895
|View full text |Cite
|
Sign up to set email alerts
|

Previous Dengue Infection and Mortality in Coronavirus Disease 2019 (COVID-19)

Abstract: We studied 2351 participants with COVID-19, 1177 (50%) reported previous dengue infection. Those without previous dengue had a higher risk of death (hazard ratio: 0.44; 95% CI: 0.22 to 0.89; p = 0.023) in 60-day follow-up. These findings raise the possibility that dengue might induce immunological protection against SARS COV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 10 publications
1
29
0
6
Order By: Relevance
“…No matter how worse the COVID-19 pandemic, countries should pay attention to the prevention and control of dengue, especially in low-income countries where dengue fever is prevalent. Considering that COVID-19 and dengue might share the similar clinical manifestations that affect the medical control and diagnosis (31,(44)(45)(46) and the overlap outbreak will lead to competition for medical resources (47)(48)(49)(50), countries should formulate strategies for their own situation and strictly control the dengue epidemic. The data collection of this study is limited.…”
Section: Discussionmentioning
confidence: 99%
“…No matter how worse the COVID-19 pandemic, countries should pay attention to the prevention and control of dengue, especially in low-income countries where dengue fever is prevalent. Considering that COVID-19 and dengue might share the similar clinical manifestations that affect the medical control and diagnosis (31,(44)(45)(46) and the overlap outbreak will lead to competition for medical resources (47)(48)(49)(50), countries should formulate strategies for their own situation and strictly control the dengue epidemic. The data collection of this study is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Patients without previous dengue had a higher risk of death (hazard ratio: 0.44; 95% confidence interval: 0.22 to 0.89; p = 0.023) at the 60-day followup. These findings have raised the possibility that dengue may induce immunological protection against SARS-CoV-2 [161].…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…The study observed decreased mortality among covid patients who had previously experienced symptomatic dengue infection (hazard ratio: .44; 95%, confidence interval: .22-.89; P = .023) in a 60-day record. It is suggested the possibility that dengue might encourage immunological safety against severe SARS-CoV-2 virus infection [37] . Nicolelis et al Observed an inverse relationship between Covid-19 and dengue cases in the regions around Asia, islands in the pacific, Latin America, and Indian oceans.…”
Section: Covid-19 Patients With Previous Dengue Infectionmentioning
confidence: 99%